1996
DOI: 10.1128/cdli.3.1.37-41.1996
|View full text |Cite
|
Sign up to set email alerts
|

Effect of malnutrition on serum and milk antibodies in Zairian women

Abstract: Serum and human milk antimicrobial antibody titers were measured longitudinally in 17 malnourished and 14 control Zairian women during 6 to 18 months of lactation to test whether malnutrition is specifically associated with an impaired secretory antibody response. No decreases in total serum and human milk immunoglobulin concentrations, neutralizing antibody titers against rotavirus, or specific enzyme-linked immunosorbent assay antibody titers against rotavirus, respiratory syncytial virus, Escherichia coli, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
0
11
1
Order By: Relevance
“…Miller (2011) found that poorly nourished Kenyan women had mean breastmilk IgA levels lower than published values for Western women. In contrast, Brussow (1996) found that immunoglobulin titers to specific infections were detectable in both well‐ and poorly nourished Zairian women; however, malnourished women had lower milk outputs, which lowered the volume of immunoglobulins ingested by infants. One study found significantly lower breastmilk IgA in poorer rural Guatemalans compared to better‐off urban women (Cruz et al, 1982); on the other hand, lower socioeconomic status has been associated with higher breastmilk IgA in US populations (Groer et al, 2004).…”
Section: Investment In Reproduction or Maintenance: A Life History Pementioning
confidence: 96%
“…Miller (2011) found that poorly nourished Kenyan women had mean breastmilk IgA levels lower than published values for Western women. In contrast, Brussow (1996) found that immunoglobulin titers to specific infections were detectable in both well‐ and poorly nourished Zairian women; however, malnourished women had lower milk outputs, which lowered the volume of immunoglobulins ingested by infants. One study found significantly lower breastmilk IgA in poorer rural Guatemalans compared to better‐off urban women (Cruz et al, 1982); on the other hand, lower socioeconomic status has been associated with higher breastmilk IgA in US populations (Groer et al, 2004).…”
Section: Investment In Reproduction or Maintenance: A Life History Pementioning
confidence: 96%
“…For instance, if offspring request more care, they may perform more nutritive and non‐nutritive suckling bouts that would, in turn, promote extra maternal care through extra maternal production of prolactin. In contrast, mothers that deteriorate in condition may experience difficulty in nursing offspring (Brussow et al. 1996), and by preventing offspring to suckle their teats, mothers may reduce prolactin concentration and thereby related maternal behaviour (Bridges et al.…”
Section: Why Did Natural Selection Not Favour a Less Costly Mechanismmentioning
confidence: 99%
“…34 A study comparing breast milk from Zairian malnourished women with healthy controls found comparable secretory IgA (sIgA) antibody titres against rotavirus, respiratory syncytial virus, Escherichia coli, S. pneumoniae and Haemophilus influenzae but an approximately 30% decrease in the amount of breast milk. 35 Hence, the quantity of antibodies and innate factors delivered to the newborn in maternal milk was reduced. When lactoferrin, lysozyme and sIgA levels were serially evaluated in breast milk from mothers with healthy babies and mothers with septicaemic babies, the breast milk from mothers with healthy babies had rapidly declining sIgA titres that were replaced by lactoferrin and lysozyme (blocks bacterial binding and lyses bacterial cell walls).…”
Section: Maternal Malnutritionmentioning
confidence: 99%
“…A study comparing breast milk from Zairian malnourished women with healthy controls found comparable secretory IgA (sIgA) antibody titres against rotavirus, respiratory syncytial virus, Escherichia coli , S. pneumoniae and Haemophilus influenzae but an approximately 30% decrease in the amount of breast milk 35 . Hence, the quantity of antibodies and innate factors delivered to the newborn in maternal milk was reduced.…”
Section: Impact Of Maternal Health On Childhood Immunitymentioning
confidence: 99%